Analysis of the Implementation of Simple Laws as an Efficiency Effort to Resolve Civil Disputes - Salim, Stefano; Capello, Julio; Rania, Andi; Chae, Suhan; Sabatini, Angel (Green Publisher Indonesia, 2025)
Conventional civil litigation in Indonesia has long faced chronic challenges in the form of slow, complicated, and expensive processes. In response, the Supreme Court launched a breakthrough in procedural law through Supreme Court Regulation (PERMA) Number 2 of 2015, which was revised by PERMA Number 4 of 2019 concerning Procedures for the Settlement of Small Claims. This regulation aims to realize the principle of simple, fast, and low-cost justice, especially for disputes with limited material value. This research uses a library research method with a juridical-normative approach to analyze the implementation of PERMA. The analysis reveals that although the small claims law (GS) has succeeded in creating significant procedural efficiencies at the examination stage—primarily through the 25-day time limit and the simplification of procedural law—its implementation in the field has not achieved holistic efficiency. Three main obstacles were identified: inconsistent compliance with the 25-day deadline across courts, the “paradox of proof” that allows defendants to complicate evidence and lead to inadmissibility rulings, and the “irony of execution” where fast decisions must still be enforced through slow general procedures due to the lack of a special execution mechanism in PERMA. This study concludes that efficiency is realized only at the examination stage and recommends amending PERMA to introduce a simpler execution mechanism, as well as optimizing the use of immediate decisions (uitvoerbaar bij voorraad) by judges as a practical solution.